DIDACTIC PRINCIPLES OF MATHEMATICS TEACHING METHODOLOGY IN PRIMARY CLASSES (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
In this article, the specific features of the structure of the mathematics course in the primary grades of the school, its content, methods of teaching mathematics in the primary grade, methods used to increase the effectiveness of teaching, forms of organizing the teaching of mathematics in the primary grade , the content of the structure and lesson system of the mathematics lesson in the primary grade, didactic principles, mathematics teaching tools and their tasks, and the features of mathematics teaching in schools with few sets are covered.